Progression to degenerative dementia in mild cognitive impairment patients: a cohort study - Feldberg, Carolina (2019)
Background: Mild cognitive impairment (MCI) is a controversial clinical entity, conceptualized as a transitional zone between normal aging and dementia. Socio-demographic and genetic factors have been involved in the development of cognitive impairment and its progression to dementia. The aim of the present study is to describe the rate of conversion to dementia in a cohort of patients with mild cognitive impairment.Method: Design Prospective cohort. Setting: A cohort of subjects with MCI was assessed and followed for three years (2013-2015) in a private institution dedicated to neurology. Participants: Patients with cognitive complaints over 60 years old who consulted spontaneously and met the MCI criteria without commitment in activities of daily living, were included consecutively and followed up annually for 3 years. Variables: Dementia and MCI were defined according to DSM IV criteria. Statistical methods we describe conversion rate as a proportion with confidence interval (CI) 95%. Bivariate analysis was performed between dementia and sociodemographic predictors and Odds Ratio and CI was calculatedResults: We include 82 subjects with MCI (age: 76.6±6.9 years, 67% women, education: 11.5±3.7 years) 4 participants were lost to follow-up. The conversion rate to dementia was 14.1% (CI95% 7.7 to 23.2) In the bivariate analysis we compared the median baseline IQ of the patients who developed dementia (97; IQR 89-103) and those who did not (93; IQR 85-95) and we obtained a significant difference with a p = 0.040Conclusions: The conversion rate to dementia in this Latin American population is coincident with studies conducted in other populations. A larger sample size is required to establish the possible predictors of conversion to dementia.